HADIS TENTANG KEUTAMAAN BAGI WANITA SALAT DI RUMAH: STUDI FIQH AL-HADÃTS - Fitriahani, Fitriahani (Jurnal Studia Insania, 2013)
This article discuses two texts of the prophetic tradition (hadith) commanding Muslim woman to pray at home rather than in mosque. The first hadith says that women are advised to pray at home. The second hadith states that, it is forbidden to prevent women from going to mosque. Both hadiths are authentic because they are reported by the authorities such as Bukhari, Muslim, Abu Dawud, Ahmad and Hakim. This means that they do not contradict each other. The first hadist means that, it is better for woman to pray at home rather than in mosque if going to the mosque will trigger immoral behaviour (fitnah). The second hadith means that, women are not forbidden to pray in mosque. Praying in mosque is good for them as far as it does not trigger immoral behaviour.